Understanding Visual Illiteracy: A Study of Comprehension of Pictorial Messages Among Farmers - Clifford Scherer (Journal of Applied Communications, 1987)
Review of "Understanding Visual Illiteracy: A Study of Comprehension of Pictorial Messages Among Farmers," publication based on the thesis by Milton Munoz, edited by Richard Powers.